(untitled) (Edad Media. Revista de Historia, 2017)
This essay is concerned with the different meanings attached to the Common Good principle in the political dynamics of the Castilian Councils in the fifteenth and sixteenth centuries. A polysemic concept that reproduces the qualities of the different orders into which that society is organized, the Common Good principle means something different for both the privileged elites and the common members of the concejo or council. The identification of these differing and contradictory uses allows us to understand the dialogue established between the different social groups and the political action at work in the cities.